LQ45 Share Return Determinants In Indonesia - Darsyah, Rahmawan; Sukarno, Hari; Sri Utami, Elok (International Journal of Scientific Research and Management (IJSRM), 2020)
Return is the result obtained from investment. Returns can be in the form of realized returns that have occurred or expected returns that have not occurred but are expected to occur in the future. Return realization (realized return) is the return that has occurred. Realized return is calculated based on historical data. Return realization is important because it is used as a measure of the company's performance. This return history is also useful as a basis for determining the expected return and risk in the future. Expected return is the return expected by investors in the future. In contrast to realized returns which have already occurred, expected returns have not yet occurred. The performance measurement was also carried out at the LQ45 company. In general, this study aims to synthesize whether the current ratio, equity ratio, dividend payout ratio, dividend yield, earnings per share, price book value, return on assets and total asset turnover are partially determinants of stock return variability. The population in this study were non-banking companies included in the LQ45 according to a circular number: Peng-00028 / BEI.OPP / 01-2018 dated January 25, 2018. Non-bank companies were chosen because the types of products produced were not in the form of services. Hypothesis testing uses multiple linear regression analysis test tools. After analyzing the data, several conclusions can be drawn, namely: only the current ratio, equity ratio, dividend payout ratio, dividend yield, return on assets and total asset turnover partially determine stock returns